Pengaruh Komunikasi, Lingkungan Kerja, Pengembangan Karir, Motivasi, dan Kompensasi Terhadap Kinerja Pegawai Perangkat Desa di Kecamatan Kabat Banyuwangi - Wines Ria Maya Devi; Saiful Amin; Muhdar Muhdar (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of communication, work environment, career development, motivation, and compensation on the performance of village equipment employees in Kabat District, Banyuwangi Regency. A descriptive quantitative approach was used, with multiple linear regression as the analytical method. The sample consisted of 60 respondents from five developed and independent villages: Pakistaji, Tambong, Dadapan, Kalirejo, and Pendarungan. The results show that among the five variables examined, only motivation and compensation have a positive and significant influence on employee performance. Meanwhile, communication, work environment, and career development were found to have no significant effect. This study recommends that village governments prioritize strategies that enhance employee motivation and provide fair compensation to improve employee performance effectively.